Innovative training on deep learning implementation: applying mindful, meaningful, and joyful learning and assessment for/as/of learning - Tiok Wijanarko; Ika Sandra; Hana Shilfia Iraqi; Yaumi Aulia Fadira; Windu Tri Mukherna (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2026)
This training aimed to enhance elementary school teachers’ competence in developing deep learning-based teaching modules and assessments aligned with the Merdeka Curriculum. The method applied was Participatory Action Research (PAR), consisting of problem identification, planning, training, observation, and reflection stages. Results showed a significant improvement in teachers’ understanding and skills, as reflected in the difference between pre-test and post-test scores. Teachers successfully produced deep learning-based teaching modules and assessment instruments packaged in digital flipbook format. They also demonstrated the ability to design contextual learning that fosters higher-order thinking skills. The program was integrated into the School Principals’ Working Group (MKKS) agenda to ensure sustainability and broader impact. Therefore, the training proved effective in strengthening teachers’ professional capacity and improving the quality of elementary school education.